Resilient Intelligence: AI and MIS in the Cyber-Economic Era - Rezwan Moin Ahsan; Borhan Uddin; Tawhid Hossen; Sachin Das (Eastasouth Institute, 2025)
The integration of artificial intelligence (AI) with management information systems (MIS) has transformed how countries protect their digital infrastructure, oversee organizational projects, and maintain economic resilience. This study consolidates recent developments in cybersecurity, project governance, software quality assurance (QA), energy analytics, and economic intelligence to propose an integrated model, AI-for-MIS Cyber-Energy-Economic Resilience (AM-CEER), that improves proactive defense, predictive governance, and sustainable performance. This research synthesizes over seventy recent peer-reviewed works, incorporating deep learning models (LSTM, Transformer), federated analytics, explainable AI (XAI), and cloud-based MIS infrastructures into a cohesive framework. Research demonstrates that AI-enhanced MIS infrastructures enhance cyber threat detection accuracy by more than 30%, diminish IT project risk exposure by 25%, and elevate predictive capability for energy and economic systems by around 40%. The proposed AM-CEER architecture creates a framework for digital governance that integrates data-driven decision-making with cybersecurity, quality assurance automation, and macroeconomic forecasting, thereby ensuring the long-term stability of essential national services.